Cellular, molecular and genomic alterations in the hatchlings of Labeo rohita after exposure to Triclosan - Sharma, Sunil; Dar, Owias Iqbal; Andotra, Megha; Sharma, Simran; Bhagat, Ankeet; Thakur, Sharad; Kesavan, Anup Kumar; Kaur, Arvinder (Frontiers in Environmental Science, 2022)
Triclosan 5-chloro-2-(2, 4-dichlorophenoxy) phenol (TCS) is widely used as a biocide in human and veterinary medicines, personal care products and household articles. To obtain biomarkers for the acute stress of Triclosan, the hatchlings of Labeo rohita were exposed for 96 h to 0.06, 0.067 and 0.097 mg/L TCS. Morphological deformities, cell viability, frequency of micronucleated and aberrant cells, transcriptomic and biomolecular alterations were recorded after exposure and a depuration period of 10 days. The exposed hatchlings had a pointed head, curved trunk, lean body, deformed caudal fin, haemorrhage, hypopigmentation and tissue degeneration at 0.067 and 0.097 mg/L only. The frequency of viable cells declined but that of necrotic, apoptotic, micronucleated and abnormal cells increased (p ≤ 0.01) in a concentration dependent manner after exposure as well as the depuration period. After recovery, the frequency of viable and micronucleated cells increased, but that of necrotic, apoptotic, and aberrant cells declined in comparison to their respective 96 h values. The mRNA level of HSP47, HSP70, HSc71 and α-tropomyosin increased (p ≤ 0.01), while that of HSP60, HSP90, DHPR, myosin light polypeptide 3, desmin b and lamin b1 declined (p ≤ 0.01) after exposure. Ten days post exposure, a significant increase (p ≤ 0.01) over control was observed in the expression of all the heat shock and cytoskeletal genes and the values (except for HSc71) were higher than the respective 96 h values also. Infrared spectra showed that band area of amide A, amide I, amide II and phospholipids increased significantly (p ≤ 0.01) but peak intensity of lipid, glycogen and nucleic acids decreased after exposure. After recovery, area of the peaks for most of the biomolecules [except lipids (2924–2925, 1455–1457 cm−1) and glycogen (1163–1165 cm−1)] declined significantly over control and 96 h values. Collectively these changes seem to be responsible not only for the onset of paralysis but also for the concentration dependent increase in larval and cellular abnormalities as well as no/sporadic swimming movement in exposed hatchlings. It is evident that HSP60, HSc71, HSP90, α-tropomyosin and DHPR were strongly affected but DHPR can be used as the most sensitive marker for the toxicity of TCS. This is the first study reporting effect of TCS on the selected heat shock and cytoskeletal genes in a single model.